Significance of variable viscosity and thermal conductivity on the dynamics of MHD cross nanofluid over a stratified Darcy-Forchheimer porous surface of a paraboloid of revolution subjected to entropy generation. (December 2022) - Rooman, Muhammad; Jameel, Muhammad; Tassaddiq, Asifa; Shah, Zahir; Alshehri, Ahmed; Kumam, Poom
Abstract: In this study, the flow of Cross fluid across gradually stratified paraboloids of revolution along with Cu-Water nanofluid was valued in relative to Darcy-Forchheimer, MHD, and various fluids properties. Stratification, rectilinear thermal emission, viscous and joule dissipation have all been considered in heat transfer equations, while chemical reaction is investigated in mass transfer equation. This article also looks at Bejan number and entropy creation. Using the proper similarity modification, the main equations of momentum, energy, and concentration are converted to system ODEs. This system of equations are mathematically explained by employing Shooting method scheme (bvp4c). The influence of important aspects of various profiles is revealed and investigated. The impact of velocity profile, temperature, concentration, entropy formation rate, and Bejan number is examined graphically. Tables are employed to display the skin friction, Nusselt number, and Sherwood number characteristics for a range of constraints. From graphical outcomes it is deduced that the velocity enhanced when the volume fraction and fluid parameter rise, whereas, for rising magnetic and porosity parameter the velocity profile dropped. The temperature profile declined when the volume fraction and thermal stratification parameter enhanced, whereas, contrasting behavior is observed for magnetic parameter and heat generation parameter. Entropy generation and Bejan number results show contrast. The Skin friction decreases and Nusselt number increases for higher volume fraction values. Sherwood number increases for higher chemical reaction parameter values.